Pictorial and verbo-pictorial metaphor in Spanish political cartooning - Negro Alousque, Isabel (Círculo de Lingüística Aplicada a la Comunicación, 2014)
In the last forty years the development of the Cognitive Metaphor Theory (Lakoff 1987, 2006, Lakoff & Johnson 1980) has given rise to a great amount of research into metaphor. The study of verbal metaphor was followed by several investigations into visual and multimodal metaphor (Forceville 2007, 2008, 2009). Whereas monomodal metaphor occurs in a single mode of representation, for instance verbal metaphor, pictorial metaphor or auditory metaphor, multimodal metaphor occurring in diverse modes, for instance verbo-pictorial metaphor. In much the same way, there have been numerous studies on metaphor-metonymy interaction cases in specialized genres. In the present article we explore monomodal visual and multimodal verbo-pictorial metaphors, and multimodal cases of metaphor-metonymy interaction (i.e. verbo-pictorial metonymy-based metaphors) in a corpus of Spanish print political cartoon strips drawn from the popular newspaper El País.